Diagnostic yield of endomicroscopy for dysplasia in primary sclerosing cholangitis associated inflammatory bowel disease: a feasibility study - Dlugosz, Aldona; Barakat, Ammar Mohkles; Björkström, Niklas K.; Öst, Åke; Bergquist, Annika (Endoscopy International Open, 2016)
Background and study aims: Primary sclerosing cholangitis associated inflammatory bowel disease (PSC-IBD) is characterized by a high risk of colorectal dysplasia. Surveillance colonoscopies with random biopsies have doubtful power for dysplasia detection. Our aim was to prospectively investigate the feasibility and efficacy of pCLE in surveillance colonoscopies in patients with PSC-IBD.Patients and methods: Sixty-nine patients with PSC-IBD underwent colonoscopy in 2 steps. On the way from rectum to cecum, the mucosa was inspected with high definition endoscopy (HDE) and random biopsies were taken according to the standard routine. On the way from cecum to rectum, fluorescein-enhanced pCLE and chromoendoscopy were performed. Regions where random biopsies had been taken, as well as visible lesions, were examined with pCLE and targeted biopsies were taken of lesions suspicious for dysplasia. Two investigators, blinded to histology and endoscopy results, analyzed all pCLE videos off-line.Results: Nineteen biopsies obtained in 13 patients (17 targeted biopsies, 2 random biopsies) revealed the presence of low-grade dysplasia. Thirteen lesions with dysplasia were endoscopically visible but by using pCLE-targeted biopsies, additional endoscopically invisible dysplasias in 4 biopsies obtained from 3 patients were detected. The sensitivity, specificity, and accuracy of pCLE in predicting dysplasia were respectively 89 % (95 % CI: 65 – 98), 96 % (95 % CI: 94 – 97), and 96 % (95 % CI: 94 – 97). pCLE showed a good performance for differentiating neoplastic from non-neoplastic mucosa with negative predictive value of 99 %. Conclusions: pCLE in PSC-IBD surveillance is feasible and may be a good complement to HDE. Future research should aim at elucidating whether real-time pCLE is applicable in PSC-IBD surveillance.